PERENCANAAN STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI UNTUK SEKOLAH MENENGAH KEJURUAN MENGGUNAKAN METODOLOGI WETHERBE: STUDI KASUS SMK AVICENA RAJEG - Supriyanto, Bambang Eko (Lembaga Penerbitan Universitas Esa Unggul, 2018)
Currently education especially at the secondary level namely SMK growing very fast. This is seen from the number of new vocational high school who stood by offering packages and diverse educational services, and accompanied by high demand of education. However a good vocational high school management is needed to keep growth in the midst of intense competition. Therefore, this research is subject to be work through of making a strategic planning IS/IT for vocational high school by use of wetherbe,s methodology. This metodologies have been rated as one of the most appropriate approuch to school organization. Results and targets to be achieved in this study is a strategic plan IS/IT in which load academic school application ranging from registration until to the graduated application, who will be expected to improve the quality and competitive advantage of school.Ã‚Â Keywords: Strategic planning IS/IT, Wetherbe's methodology, SMK Avicena Rajeg